2022
DOI: 10.1049/hve2.12188
|View full text |Cite
|
Sign up to set email alerts
|

Streamer dynamics and charge self‐erasing of two counter‐propagating plasmas in repetitively pulsed surface dielectric barrier discharge

Abstract: The streamer dynamics and charge self‐erasing of two counter‐propagating plasmas generated by repetitively pulsed surface dielectric barrier discharge are investigated using electrical and optical diagnosis, and a two‐dimensional fluid model. Three distinct discharge phases of primary, transitional and secondary streamers are identified in a single‐pulse discharge through the time‐resolved plasma images. Moreover, a merging phenomenon of the two opposing primary streamers is observed at the middle position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Based on the above discussion, it was concluded that the H-DBD generated in N 2 was due to the high concentration of seed electrons generated through Penning ionisation between two N 2 metastable molecules via reactions ( 8) and (9).…”
Section: N 2 H-dbd (1) N 2 Metastable Penning Ionisation Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Based on the above discussion, it was concluded that the H-DBD generated in N 2 was due to the high concentration of seed electrons generated through Penning ionisation between two N 2 metastable molecules via reactions ( 8) and (9).…”
Section: N 2 H-dbd (1) N 2 Metastable Penning Ionisation Hypothesismentioning
confidence: 98%
“…Non-equilibrium atmospheric pressure plasma (N-APP) is a promising technology for generating high concentration reactive species at a relatively low gas temperature or room temperature [1-8], making it highly attractive for a variety of applications such as surface modification, decontamination of temperature-sensitive materials, and more [9][10][11][12][13][14][15]. Among the different methods used for generating N-APP, dielectric barrier discharge (DBD) is one of the most widely studied techniques and has been explored for more than a century [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric barrier discharge (DBD), as a typical NTP, has great potential for treating VOCs at high concentrations (>1000 ppm) [11][12][13][14]. Most research on VOC degradation by DBD plasma focuses on reducing energy consumption while improving the degradation efficiency of target substances.…”
Section: Introductionmentioning
confidence: 99%
“…They are formed at high gas pressures, in particular at atmospheric pressure. Due to the prospects of using atmospheric pressure discharges in a wide variety of fields of science and technology, significant success has been achieved both in the modelling of streamer discharges using particle-in-cell methods [11][12][13], fluid models [14][15][16][17] including nanosecond atmospheric discharges [18][19][20], experimental studies [21][22][23][24], and their combinations [25][26][27][28][29]. Special attention has been paid to nanosecond discharges in gases of atmospheric pressure in an inhomogeneous electric field, as a fairly simple method for producing a low-temperature non-equilibrium plasma.…”
Section: Introductionmentioning
confidence: 99%